Pengaruh Lama Penyangraian Terhadap Karateristik Kimia dan Mutu Organoleptik Pasta Cokelat - Prasetyo, Muhammad Dwi; nengsih, yulistiati; Marpaung, Ridawati; Andriyani, Lizyanti (Universitas Batanghari, 2024)
Roasting is a very important post-harvest stage in processing cocoa beans into derivative products because this roasting process will produce the characteristic color, aroma, taste and texture of the cocoa beans. The research was carried out from February to March 2023 at the Basic Laboratory of Batanghari University, Jambi. The study used a completely randomized environmental design. The treatment design is roasting time with 4 levels as follows: P1: 20 minutes, P2: 30 minutes, P3: 40 minutes, P4: 50 minutes. The variables observed were the moisture content of the dry cocoa beans, the color of the chocolate paste, the aroma of the chocolate paste, the taste of the chocolate paste, the liking of the chocolate paste, the bitterness of the chocolate paste. Organoleptic testing of color, aroma, taste, brownness and liking variables was carried out using a perception test with a 5-scale Likert scale. The data was tabulated, followed by analysis of variance, then continued with the DMRT test at the Î± level of 5%. Based on the results of the research and discussion, it can be concluded that different roasting times have no significant effect on the acidity (pH) of roasted cocoa beans, color, aroma, taste, bitterness and liking of chocolate paste. Roasting time of 20 minutes produces chocolate paste with a brown color, a favorable aroma, a favorable taste, a slightly bitter bitterness level and a favorable level of liking.Â